Ketika Gratis Tak Cukup: Eksperimen Pengaruh Harga dan Waktu Tunggu terhadap Keputusan Membeli - Resekiani Mas Bakar; Hairunnisa Putri Ramadhani Darwis; Nur Khairunnisa; Elda Hasya (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to examine the effects of price variation and waiting time on consumers’ purchase decisions within the framework of the zero price effect. The research involved 50 randomly selected housewives, both employed and non-employed. A 2×2 between-subjects factorial experimental design was used, manipulating two independent variables: price (free vs. discounted) and waiting time (present vs. absent). Data were collected through an online shopping simulation, and purchase decisions were measured by click-to-buy or cancellation actions. The data were analyzed using chi-square tests and binary logistic regression. Results showed no significant difference between the free and discounted price conditions, and no significant effect of waiting time on purchase decisions. Additionally, no interaction effect between price variation and waiting time was found. These findings suggest that the effect of time as a non-monetary sacrifice is not always significant, and marketing strategies should be tailored to the specific context of the consumer.